PENGARUH REWARD, PROFESIONALISME PROFESI, DAN MORAL TERHADAP INTENSITAS AUDITOR INTERNAL MELAKUKAN WHISTLEBLOWING - Elimanto, Lie Sugiono; Mulia, Teodora Winda (Widya Mandala Surabaya Catholic University, 2016)
At this time a lot of fraud in the company that carried out by one or several people, either for personal benefit or the benefit of the company. Generally internal auditor is obliged to find and report fraud, but whistleblowing can be done by various profession-als who know about the cheating that occurred. Reward, the professionalism of the profession, and morals are three of the many things that affect a person's intention to report the fraud he knows. Reward will generally make a person interested to report fraud, attracted by the rewards that will be obtained. Professionalism profession would make one report fraud, because they feel it is an obligation of duty. High morals would make someone do something right, as reported fraud occurring. Based on the respond-ents coming from the internal auditor in Surabaya, the result that the professionalism of the profession and moral influence the intensity of the internal auditor to conduct whistleblowing, while the reward has no effect on the intensity of the internal auditors do whistleblowing, on industrial property and real estate.